The biomechanics of concussion for ice hockey head impact events. Issue 6 (26th April 2019) - Post, Andrew; Hoshizaki, T. Blaine; Karton, Clara; Clark, J. Michio; Dawson, Lauren; Cournoyer, Janie; Taylor, Karen; Oeur, R. Anna; Gilchrist, Michael D.; Cusimano, Michael D.
Abstract: The purpose of this research was to conduct reconstructions of concussive and non-concussive impacts in ice hockey to determine the biomechanics and thresholds of concussive injury in ice hockey. Videos of concussive and non-concussive impacts in an elite professional ice hockey league in North America were reconstructed using physical and finite element model methods. Eighty concussive and 45 non-concussive events were studied. Logistic regressions indicate significant thresholds for concussion for linear/rotational acceleration and CSDM10% . Impacts in ice hockey were mostly long duration events, longer than 15 ms. These results have significant implications for helmet standards and development to prevent concussion.